Attenuating Mutations in Coxsackievirus B3 Map to a Conformational Epitope That Comprises the Puff Region of VP2 and the Knob of VP3 - Stadnick, E. (American Society for Microbiology, 2004)
Ten antibody escape mutants of coxsackievirus B3 (CVB3) were used to identify nucleotide substitutions that determine viral virulence for the heart and pancreas. The P1 region, encoding the structural genes of each mutant, was sequenced to identify mutations associated with the lack of neutralization. Eight mutants were found to have a lysine-to arginine mutation in the puff region of VP2, while two had a glutamate-to-glycine substitution in the knob of VP3. Two mutants, EM1 and EM10, representing each of these mutations, were further analyzed, initially by determining their entire sequence. In addition to the mutations in P1, EM1 was found to have two mutations in the 3D polymerase, while EM10 had a mutation in stem-loop II of the 5′ nontranslated region (5′NTR). The pathogenesis of the mutants relative to that of CVB3 strain RK [CVB3(RK)] then was examined in A/J mice. Both mutants were found to be less cardiotropic than the parental strain, with a 40-fold (EM1) or a 100- to 1,000-fold (EM10) reduction in viral titers in the heart relative to the titers of CVB3(RK). The mutations in VP2, VP3, and the 5′NTR were introduced independently into the RK infectious clone, and the phenotypes of the progeny viruses were determined. The results substantiated that the VP2 and VP3 mutations reduced cardiovirulence, while the 5′NTR mutation in EM10 was associated with a more virulent phenotype when expressed on its own. Stereographic imaging of the two mutations in the capsomer showed that they lie in close proximity on either side of a narrow cleft between the puff and the knob, forming a conformational epitope that is part of the putative binding site for coreceptor DAF.